1970
DOI: 10.1017/s0022172400042492
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation, persistence and dispersal of foot-and-mouth disease virus by man

Abstract: SUMMARYSampling of human subjects, who had been in contact with animals infected with foot-and-mouth disease (FMD) virus, showed that virus could be recovered from the nose, throat, saliva and from air expelled during coughing, sneezing, talking and breathing. The amounts of virus recovered paralleled those collected with a large-volume sampler and multistage impinger and these findings confirmed that the highest recovery of airborne virus was from infected pigs followed by cattle and sheep. More virus was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 10 publications
1
31
2
1
Order By: Relevance
“…Table 3 provides a summary of both key findings and suggested future research. Other potential sources of infectious FMDV aerosols were not ruled out by this study, nor by an earlier study [67] that reported more virus recovered from the noses of animal handlers examining the head relative to other handlers examining other body regions. 2 Measurements reported here were taken near human habitats.…”
Section: Discussionmentioning
confidence: 70%
“…Table 3 provides a summary of both key findings and suggested future research. Other potential sources of infectious FMDV aerosols were not ruled out by this study, nor by an earlier study [67] that reported more virus recovered from the noses of animal handlers examining the head relative to other handlers examining other body regions. 2 Measurements reported here were taken near human habitats.…”
Section: Discussionmentioning
confidence: 70%
“…Sellers et al (35) demonstrated that workers who had been handling pigs at the height of infection and who had a dose of loglo2.7 IDso of virus in their noses were able to transmit the virus to a colleague, in whose nose a dose of loglo1.3 IDso was found. They were also able to transmit virus to a susceptible steer after following standard disinfection procedures.…”
Section: Transmission By Peoplementioning
confidence: 99%
“…Smith & Hugh-Jones (1969) examined the epidemic in detail and reported on the weather elements involved. In the light of recent findings on the factors involved in airborne spread of footand-mouth disease (Sellers & Parker, 1969;Donaldson, Herniman, Parker & Sellers, 1970; Sellers, Donaldson & Herniman, 1970; Sellers, 1971; Sellers, Herniman & Donaldson, 1971; Barlow, 1972;Donaldson, 1972;Sellers & Herniman, 1972), we decided to re-examine the course of the epidemic.…”
Section: Introductionmentioning
confidence: 99%